Cost-Effectiveness Analysis of Direct Oral Anticoagulants Versus Vitamin K Antagonists for Venous Thromboembolism in China - Sun, Ke-Xin; Cui, Bin; Cao, Shan-Shan; Huang, Qi-Xiang; Xia, Ru-Yi; Wang, Wen-Jun; Wang, Jing-Wen; Yu, Feng; Ding, Yi (Frontiers in Pharmacology, 2021)
Background: The drug therapy of venous thromboembolism (VTE) presents a significant economic burden to the healthcare system in low and middle-income countries. To understand which anticoagulation therapy is the most cost-effective for clinical decision-making, the cost-effectiveness of apixaban (API) versus rivaroxaban (RIV), dabigatran (DAB), and low molecular weight heparin (LMWH) followed by vitamin K antagonist (VKA) in the treatment of VTE in china were assessed. Methods: To access the quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratios (ICERs), a long-term cost-effectiveness analysis was constructed using a Markov model with 5 health states. The Markov model was developed using patient data collected from the Xijing Hospital from January 1, 2016, to January 1, 2021. One way and probabilistic sensitivity analyses (PSA) were used to test the uncertainties. A Chinese healthcare system perspective was taken. Results: In the base case, data of 231 VTE patients were calculated in the base case analysis retrospectively. RIV group resulted in a mean VTE attributable 95% effective treatment. The API, DAB, and VKA have a negative ICER (-187017.543, -284674.922, -9283.339) and were absolutely dominated. Markov model results confirmed this result. The ICER of the API and RIV was negative (-216176.977), which belongs to the absolute inferiority scheme; and the ICER value of the DAB and VKA versus RIV is positive (110577.872 and 836846.343). Since the ICER of DAB and VKA exceeds the threshold, RIV therapy was likely to be the best choice for the treatment of VTE within the acceptable threshold range. The results of the sensitivity analysis revealed that the model output varied mostly with the cost in DAB on-treatment therapy. In a probabilistic sensitivity analysis at 1000 patients for 30 years, RIV has 100%probability of being cost-effective compared with other regimens when the WTP is 10973 per QALY. When WTP exceeded 148,000, DAB was more cost-effective than RIV. Conclusions: Compared with LMWH+VKA and API, the results proved that RIV may be the most cost-effective treatment for VTE patients in China. Our findings could be helpful for physicians in clinical decision-making to select the appropriate treatment option for VTE.